Three consecutive odd numbers add up to -267
If "x" represents the first odd number, then
"x+2" represents the second number
"x+4" represents the third number
![x+(x+2)+(x+4)=-267](https://img.qammunity.org/2023/formulas/mathematics/college/slae9badbg5ut24dcjlizazyndwi9n131z.png)
From this expression, you can calculate the value of x
![\begin{gathered} x+x+x+2+4=-267 \\ 3x+6=-267 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/9lxznvv6ggrsj58gln7mvzsm4x9lomgm8a.png)
Pass 6 to the right side of the equation by subtracting it from both sides of the expression
![\begin{gathered} 3x+6-6=-267-6 \\ 3x=-273 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/s1p3a6og1vlse3s4zn81mnkc4ze93dm78i.png)
Finally divide both sides of the expression by 3 to determine the value of x
![\begin{gathered} (3x)/(3)=-(273)/(3) \\ x=-91 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/5jgcz3jssh5zfhh6sf6u2pbpohy81chgf3.png)
Now that we know the first odd number you can calculate the other two as follows:
![\begin{gathered} x=-91 \\ x+2=-91+2=-89 \\ x+4=-91+4=-87 \end{gathered}](https://img.qammunity.org/2023/formulas/mathematics/college/x25euezwwzwuqp9s43ssvy0of22avhuh48.png)
The three odd numbers that add up to -267 are -91, -89, and -87